The Effect of Work Discipline on Employee Performance at the Pandeglang City Regional Financial Management Agency - Harjanto, Lily (CV. Rayyan Dwi Bharata, 2023)
The Pandeglang City Regional Financial Management Agency (BPKD) is a government agency based on Pandeglang City Regional Regulation Number 42 of 2016 the main task of the Pandeglang City BPKD is to carry out Regional Government affairs in the field of regional financial management based on the principle of autonomy and co-administration. However, there are several problem phenomena that are occurring at this time, in relation to work discipline and employee performance at the BPKD in Pandeglang City. This study is intended to determine work discipline on employee performance at BPKD Pandeglang City. The research method used by researchers is descriptive and associative quantitative research methods. The population in this study were BPKD employees in Pandeglang City. The sampling technique in this study uses a saturated sample (census) which is part of the non-probability sampling technique. Therefore, the respondents who were used as samples in this study were 95 employees. Data collection techniques in this study used observation, interviews, documentation, and questionnaires. The data analysis techniques that the researchers will use in this study are Data Validity Tests, Reliability Tests, Correlation Coefficients, Determination Coefficients, Simple Linear Regression, and Hypothesis Tests. The results showed that there was an influence between work discipline and employee performance at BPKD Pandeglang City.